LITERATURA COMPARADA: TRANSCULTURAÇÃO E ESPAÇO PÚBLICO - Walty, Ivete Lara Camargo (Organon, 2012)
Reflections on the place of literature in the society, considering the efficient relation between the written word and the formation of the bourgeois public space, either at the time of its formation in Europe (HABERMAS, 2003) and in its late formation in Brazil (CANDIDO, 1976; SANTIAGO, 2004). Resuming the relation between the written word and other media, one intends to revisit the concept of transculturation in its relation with the concept of multiculturalism,considering the places of the illiterate people in the Brazilian cultural production. Furthermore, one aims to study possible movements and interactions among different social groups and their interventions in this space, including in it the street and the mediatic forms, and, more than that, the Comparative Literature itself in its transdisciplinary aspect.